2021
DOI: 10.3389/fimmu.2021.717998
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte Immunoglobulin-Like Receptors in Regulating the Immune Response in Infectious Diseases: A Window of Opportunity to Pathogen Persistence and a Sound Target in Therapeutics

Abstract: Immunoregulatory receptors are essential for orchestrating an immune response as well as appropriate inflammation in infectious and non-communicable diseases. Among them, leukocyte immunoglobulin-like receptors (LILRs) consist of activating and inhibitory receptors that play an important role in regulating immune responses modulating the course of disease progression. On the one hand, inhibitory LILRs constitute a safe-guard system that mitigates the inflammatory response, allowing a prompt return to immune ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 144 publications
(261 reference statements)
0
30
0
Order By: Relevance
“…Leukocyte immunoglobin-like receptors (LILRs) consists of 11 receptors with extracellular Ig-like domains, categorized into inhibitory (LILRB1-B5) and activating (LILRA1-A6 except A3) and reported to be expressed mostly in neutrophils [ 55 ]. LILRB2 suppress immune cell activity and mainly reported in viral, bacterial and parasite infection [ 56 ]. Recently it has been shown that LILRB2 is up-regulated in corneal tissues of bacterial keratitis.…”
Section: Discussionmentioning
confidence: 99%
“…Leukocyte immunoglobin-like receptors (LILRs) consists of 11 receptors with extracellular Ig-like domains, categorized into inhibitory (LILRB1-B5) and activating (LILRA1-A6 except A3) and reported to be expressed mostly in neutrophils [ 55 ]. LILRB2 suppress immune cell activity and mainly reported in viral, bacterial and parasite infection [ 56 ]. Recently it has been shown that LILRB2 is up-regulated in corneal tissues of bacterial keratitis.…”
Section: Discussionmentioning
confidence: 99%
“…The expanding LILRB field has begun to explore the importance of these receptors in immune dysregulation; however, little is known about their involvement in infection ( 89 ). As recently reviewed by Abdallah et al, a considerable number of pathogens are capable of interacting directly with LILRB family members to induce immunosuppression, which may prove especially pertinent during both ongoing and overt responses to infection ( 90 ). Conversely, blocking the interaction between LILRBs and pathogenic ligands may mitigate the immunoevasion that pathogens employ to prolong infection and perpetuate survival.…”
Section: Infectionmentioning
confidence: 99%
“…The tolerogenic capability of DCs relies on their maturation state, the presence of anti-inflammatory molecules and the type of microbial stimuli ( 6 ). The induction of immunity or tolerance depends on the balance between activating and inhibitory processes ( 7 ). Therefore, the identification of molecules that elicit immunomodulatory effects may provide new therapeutic strategies to treat infectious and malignant diseases ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…The induction of immunity or tolerance depends on the balance between activating and inhibitory processes ( 7 ). Therefore, the identification of molecules that elicit immunomodulatory effects may provide new therapeutic strategies to treat infectious and malignant diseases ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%